Consumer food safety awareness and demand for fluid milk: A case study from India - Kumar, Anjani; Mishra, Ashok K.; Sonkar, Vinay K.; Roy, Devesh (Project MUSE, 2024)
ABSTRACT: Despite significant improvements in consumers’ food safety awareness, the literature provides little or no evidence of the impact of food safety awareness on the quantity of fluid milk consumers purchased. This is especially true for India’s consumers, where the economy is changing rapidly regarding food marketing, incomes, urbanization, and increased demand for food safety.The study is based on primary data from a survey of consumers from urban and peri-urban districts in India. The survey collected information on socioeconomic characteristics, dairy consumption, purchasing patterns, and food safety awareness. This study first creates a food safety awareness (FSA) index to measure consumers’ awareness of food safety attitudes and perceptions. It investigates the factors affecting consumers’ food safety awareness and FSA’s impact on fluid milk demand. The study uses a newly developed impact evaluation method, continuous treatment matching estimation, and dose-response functions (DRFs) to assess the impact of FSA on consumers’ fluid milk purchases. Findings show that educational attainment, sources of information on food safety, age, and gender of the head of the household significantly influenced consumers’ food safety awareness. Further, the study finds that food safety awareness positively impacts the demand for fluid milk. After controlling for milk prices and family income, Indian consumers aware of and adopt seven or more food safety habits or practices are likely to demand more fluid milk. Results are robust to specifications, income levels, and the location of households. The link between food safety awareness and the quantity of milk purchased implies a latent consumer demand for food safety. Any consumer awareness programs and policies supporting milk and its products’ hygienic production will likely increase demand for milk and dairy products. At a policy level, credible systems can be put in place for food certification and labeling, which enhance the availability of safe and hygienic food.